The body thief : the death (and further adventures) of Silas Winterbottom - Giles, Stephen M. (Sourcebooks Jabberwocky, 2010)
Lured to their sick Uncle Silas's home under the pretense of becoming heirs to his vast fortune, cousins Adele, Isabella, and Milo soon learn that the old man has a diabolical plan to prevent his own death.